Cytogenetic analysis of five species of the subfamily Tetragonopterinae (Teleostei, Characiformes, Characidae) - Carvalho, Margarida Lima; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Firenze University Press, 2002)
The subfamily Tetragonopterinae is composed by a large number of species distributed in South and Central America. This subfamily has many taxonomic and phylogenetic problems, being considered by several authors as an artificial group. With the objective to better understanding the relationships among the components of this fish group, cytogenetic studies were conduced on five species of Tetragonopterinae. Astyanax janeiroensis had 2n=50 chromosomes (6M+14SM+14ST+16A), Hyphessobrycon reticulatus had 2n=50 chromosomes (14M+20SM+16ST), Hollandichthys multifasciatus had 2n=50 chromosomes (10M+12SM+28ST), Ctenobrycon hauxwellianus had 2n=50 chromosomes (10M+6SM+34ST), and Phenacogaster cf. pectinatus had 2n=46 chromosomes (12M+2ST+32A). Only A. janeiroensis had multiple NORs, while all other species had simple NORs. Small heterochromatic blocks were observed in the chromosomes of all species in a pericentromeric position. A. janeiroensis also had some chromosomes with large heterochromatic blocks in a terminal position and a pair with an interstitial block. The karyotypic evolution of each genus is discussed.
Keywords: C-band; Evolution; Fish chromosomes; Tetragonopterinae